Parasitism capacity of telenomus sp. (hymenoptera: scelionidae) on spodoptera frugiperda, in refugia system - Ardina, Ardina; Bakti, Darma; Tobing, Maryani Cyccu L.; Ubaidillah, Rosichon; Darmawan, Darmawan (International Journal of Basic and Applied Science, 2024)
Fall armyworm (Spodoptera frugiperda) is one of the pests that attacks maize. There are many ways to control this pest problem one of which is to use  insecticides. However, biological control this pest with nature conservation based on the concept of integrated pest control. Refugia plants offer pest control properties based on the IPM (Integrated Pest Management) concept by providing food for parasitoids as the natural enemies. This study aimed to know capacity parasitism of egg parasitoid S. frugiperda in refugia system. This research uses non-factorial randomized group design (RGD) study, the number of S. frugiperda egg parasitoids on maize fields with refugia plants around it was counted.  There were 5 treatments with 5 replications applied in this study: Control/without refugia, maize plants with red refugia (Zinnia elegans), maize plants with yellow refugia (Melanpodium paludosumi), maize plants with white refugia (Turnera subulata), maize plants with red refugia, yellow and white. This study found two species of S. frugiperda egg parasitoids namely Telenomus remus Nixon (Hymenoptera: Scelionidae) and Telenomus dignus (Hymenoptera: Scelionidae) in the field. The overall rate of parasitism egg S. frugiperda was no significant effect. The treatment of maize plants with white and mixed-colour refugia (red, yellow, white) showed the highest egg parasitization at 15 days after planting (DAP). Meanwhile, the dominance of Telenomus remus Nixon parasitoid was at an average of 0.202% and the lowest dominance of Telenomus dignus at 0.030%.